The complete mitochondrial genome of white-tufted-ear marmoset, Callithrix jacchus (Primates: Callitrichinae). (3rd May 2016) - Wang, Wei; Liu, Jing-Yu; Wang, Hai-Feng; Yang, Ming-Ying; Liu, Qi-Ying; Ding, Ming-Xia
Abstract: The white-tufted-ear marmoset ( Callithrix jacchus ) is a New World primate that inhabits the coastal rainforests of eastern Brazil. In the present work, we report the complete mitochondrial genome sequence of white-tufted-ear marmoset for the first time. The total length of this mitogenome is 16, 499 bp long, containing 13 protein-coding genes, 22 transfer RNA genes, 2 ribosomal RNA genes, and 1 non-coding region (D-loop region). The gene organization and arrangement is identical to typical vertebrates. The overall base composition is 32.75% of A, 26.95% of T, 26.91% C, and 13.39% G, with a slight A + T bias of 59.7%. All the genes are encoded on H-strand, except for the ND6 subunit gene and 8 tRNA genes. The complete mitochondrial genome sequence reported here will be useful for comparative genomics studies in primates.